2020
DOI: 10.20870/oeno-one.2020.54.4.3861
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to climate change by determining grapevine cultivar differences using temperature-based phenology models

Abstract: Grapevine phenology is advancing with increased temperatures associated with climate change. This may result in higher fruit sugar concentrations at harvest and/or earlier compressed harvests and changes in the synchrony of sugar with other fruit metabolites. One adaptation strategy that growers may use to maintain typicity of wine style is to change cultivars. This approach may enable fruit to develop under temperature conditions similar to those typically associated with that wine style. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…If grapes ripen too early, they can have high sugar levels and low acidity, which will lead to excessive alcohol and lack of freshness in the resulting wines. Late ripening can result in unripe grapes and wines marked by green flavours (Parker et al, 2020). We did not harvest on the same day, because the development stages of the two treatments were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…If grapes ripen too early, they can have high sugar levels and low acidity, which will lead to excessive alcohol and lack of freshness in the resulting wines. Late ripening can result in unripe grapes and wines marked by green flavours (Parker et al, 2020). We did not harvest on the same day, because the development stages of the two treatments were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Plants 2021, 10, x FOR PEER REVIEW 5 of 1412 July 2009, while the berries reached the maturation index established for harvesting at 16 July 2009; that is, four days later than predicted. If we used the typical meteorological year instead of the average year, then the prediction ability was greatly improved since harvest was forecast at 15 July 2009; that is only one day before harvesting.…”
mentioning
confidence: 92%
“…On the contrary, global warming projections indicate the anticipation of the phenological events and that plants will fulfill their heat requirements in a shorter period [ 11 ]. Climate changes also makes more difficult forecasting harvest dates [ 12 ] and planning the cultivation techniques [ 13 ]. An accurate estimation of heat requirements based on cardinal temperatures regardless the time required for its fulfillment can be helpful in this context [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent validation (Parker et al, 2020b ), the model was tested for the period 2004–2020 and it was found the goodness-of-fit (root mean squared error) was 6.67, 4.67, and 9.67 days for flowering, véraison and time to 200 g/l sugar concentrations respectively which was within prediction ranges of the original calibrations and validations of cultivars by the models (Parker et al, 2011 , 2013 , 2020a ). In addition, the temperature relationships for the GSR and GFV models have been successfully validated beyond the original model development datasets (Verdugo-Vásquez et al, 2019 ; Parker et al, 2020b ; Ramos and de Toda, 2020 ; Wang et al, 2020 ) including other cool climate areas such as Champagne (Parker et al, 2020a ) and areas in China (Wang et al, 2020 ). They have also been applied in combination with future climate change projections (van Leeuwen et al, 2019 ; de Rességuier et al, 2020 ; Parker et al, 2020b ; Ramos and de Toda, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the temperature relationships for the GSR and GFV models have been successfully validated beyond the original model development datasets (Verdugo-Vásquez et al, 2019 ; Parker et al, 2020b ; Ramos and de Toda, 2020 ; Wang et al, 2020 ) including other cool climate areas such as Champagne (Parker et al, 2020a ) and areas in China (Wang et al, 2020 ). They have also been applied in combination with future climate change projections (van Leeuwen et al, 2019 ; de Rességuier et al, 2020 ; Parker et al, 2020b ; Ramos and de Toda, 2020 ). Together, these tests and applications of the GSR and GFV models illustrate the models' broad applicability to new sites and different climates.…”
Section: Methodsmentioning
confidence: 99%